The Impulse Buying Phenomenon: A Comparative Study in Skin Care Purchase At Live Streaming Tiktok Shops Moderating By Gender - Ferry Aditya; Lenda Panambunan; Rimon Siregar; Pantri Heriyati (Return : Study of Management, Economic and Bussines, 2023)
This research aims to examine the role of social presence in live streaming TikTok Shop segmented in Indonesia on arousal and pleasure emotion that leads to consumer impulse buying who buy skincare moderated by gender. The data collection method for this research will be using quota sampling by online survey with 300 respondents as a representative sample. The results of this study showed that the role of social presence will positively influence or not positively influence impulse buying from arousal and pleasure emotion and whether the consumer gender will moderate and show any different result. It's not common to focus this study in Indonesia and focus on skincare products consumers while researching the role of social presence in live streaming TikTok Shop toward impulsive buying that are moderated by gender.